2020
DOI: 10.3389/fimmu.2020.01172
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine Acts as an Immunosuppressant by Exerting Prooxidative Effects in Human T Cells Resulting in Diminished TH17 but Enhanced Treg Differentiation

Abstract: Piperlongumine (PL), a natural small molecule derived from the Piper longum Linn plant, has received growing interest as a prooxidative drug with promising anticancer properties. Yet, the influence of PL on primary human T cells remained elusive. Knowledge of this is of crucial importance, however, since T cells in particular play a critical role in tumor control. Therefore, we investigated the effects of PL on the survival and function of primary human peripheral blood T cells (PBTs). While PL was not cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 63 publications
0
7
0
2
Order By: Relevance
“…We speculate that mtROS and mtROS-induced HIF-1a may have opposite effects in iTreg differentiation, and the final outcome depends on which of the two plays a stronger role; the nature of the initial stimulus may be crucial in this process. For instance, Liang et al showed that the natural small molecule piperlongumine enhanced iTreg differentiation by exerting prooxidative effects; however, it also strongly inhibited the expression of HIF-1α [ 39 ]. In contrast, our data showed that cholesterol notably increased HIF-1α, which may offset the promotive effect of mtROS in iTreg differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that mtROS and mtROS-induced HIF-1a may have opposite effects in iTreg differentiation, and the final outcome depends on which of the two plays a stronger role; the nature of the initial stimulus may be crucial in this process. For instance, Liang et al showed that the natural small molecule piperlongumine enhanced iTreg differentiation by exerting prooxidative effects; however, it also strongly inhibited the expression of HIF-1α [ 39 ]. In contrast, our data showed that cholesterol notably increased HIF-1α, which may offset the promotive effect of mtROS in iTreg differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Pada umumnya PIP telah banyak dimanfaatkan sebagai bioenhancer untuk meningkatkan bioavailabilitas obat yang dikombinasikan dengannya (7). Begitu pula dengan PL yang secara tradisional telah dimanfaatkan dalam pengobatan penyakit pencernaan, saluran pernafasan, dan menular seperti malaria (8). Secara tradisional TQ telah dimanfaatkan untuk mengobati banyak penyakit, misalnya asma, hipertensi, diabetes, peradangan, batuk, dan lain-lain dalam berbagai bentuk.…”
Section: Pendahuluanunclassified
“…Because TGF-β is a potent immunosuppressant affecting T lymphocytes, the release of ROS-mediated TGF-β can also contribute to the depletion of lymphocytes in COVID-19. Finally, maintaining T cells in a pro-oxidative state was shown to promote the development of Treg lymphocytes [ 114 ]. This relative increase in Tregs can also affect the ability of T cells to defend against a SARS-CoV-2 infection [ 102 ].…”
Section: Adaptive Immunity In Covid-19mentioning
confidence: 99%